2016
DOI: 10.1155/2016/6848902
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Novel Agent-Based Therapies for Multiple Myeloma: A Meta-Analysis

Abstract: This study aimed at comparing bortezomib, thalidomide, and lenalidomide in patients with multiple myeloma (MM) for safety and efficacy using meta-analysis. This meta-analysis identified 17 randomized controlled trials (RCTs) including 6742 patients. These RCTs were separated according to the different agent-based regimens and to autologous stem-cell transplantation (ASCT). Complete response (CR), progression-free survival (PFS), overall survival (OS), and adverse events (AE) were combined. The total weighted r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Since 2007, the first-line treatment of MM has changed dramatically; almost all patients (89.4%) received novel agents alone or combined with chemotherapy in 2015, and the rate of transplantation almost doubled. Over the same period, OS increased and while our study was not designed to show a causal association between treatment use and survival, the increase in OS is consistent with clinical benefit, including increased survival, associated with the use of novel agents and transplantation as demonstrated in clinical trials and epidemiological studies [11,12].…”
Section: Discussionsupporting
confidence: 61%
“…Since 2007, the first-line treatment of MM has changed dramatically; almost all patients (89.4%) received novel agents alone or combined with chemotherapy in 2015, and the rate of transplantation almost doubled. Over the same period, OS increased and while our study was not designed to show a causal association between treatment use and survival, the increase in OS is consistent with clinical benefit, including increased survival, associated with the use of novel agents and transplantation as demonstrated in clinical trials and epidemiological studies [11,12].…”
Section: Discussionsupporting
confidence: 61%
“…For example, alkylating agents also cause immune dysfunction through disproportionate depletion of CD4 + T cells, relative to CD8 + T cells [78-80]. Tyrosine kinase inhibitors increase risks for bacterial pneumonia through both neutropenia-dependent and -independent mechanisms, possibly including effects on antibody class switching [81, 82]. Anthracyclines, taxanes, topoisomerase inhibitors, and vinca alkaloids all appear capable of increasing risk of bacterial pneumonia via non-neutropenic mechanisms during treatment [83].…”
Section: Introductionmentioning
confidence: 99%
“…Using meta-analysis, Wang X compared novel-based regimens using bortezomib, thalidomide and lenalidomide in patients with myeloma for safety and efficacy. This study showed greater benefit in terms of progression-free survival of all subgroups, irrespective of whether the patient received autologous stem-cell transplantation 6. However, compared to the control group, a higher proportion of adverse events including neutropenia, thrombocytopenia, peripheral neuropathy and thrombosis occurred in the novel agent groups 6…”
Section: Discussionmentioning
confidence: 63%
“…PET/CT is indeed a valuable imaging tool for the assessment of extra-medullary involvement. Regelink's systematic review supports the International Myeloma Working Group guidelines, which recommend that whole body CT can replace whole body X-ray 6. However, additional radiographs of the skull and ribs are advised as they are often underdiagnosed by modern imaging 7.…”
Section: Discussionmentioning
confidence: 92%